Archives and transitional justice in Chile: A crucial relationship - Ferrara, Anita (Human rights review, 2021)
The article, through the case study of Chile, explores the interconnections between archives, human rights and transitional justice. Chile represents a unique case globally for the early creation of thousands of records documenting the human rights violations committed under Pinochet’s 17-year dictatorship. In post-Pinochet Chile, the human rights archives have provided extremely important sources of evidence that have proven crucial in the development of transitional justice mechanisms. Truth commissions have, in turn, created their own archives, which have strongly contributed to later processes of reparation, justice and memory. The article aims to develop a better understanding of the multiple roles that archives have played as tools for achieving truth, justice and reparation over the long transitional period in Chile. The article argues that a combination of several factors and the intervention of different actors led to the archives having a significant impact in the development of subsequent transitional justice mechanisms.